2002
DOI: 10.1039/b201366p
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic-speciation in arsenate-resistant and non-resistant populations of the earthworm, Lumbricus rubellus

Abstract: Arsenic speciation was determined in Lumbricus rubellus Hoffmeister from arsenic-contaminated mine spoil sites and an uncontaminated site using HPLC-MS, HPLC-ICP-MS and XAS. It was previously demonstrated that L. rubellus from mine soils were more arsenate resistant than from the uncontaminated site and we wished to investigate if arsenic speciation had a role in this resistance. Earthworms from contaminated sites had considerably higher arsenic body burdens (maximum 1,358 mg As kg-1) compared to the uncontami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
75
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 20 publications
(49 reference statements)
8
75
3
Order By: Relevance
“…17 However, the fact that AB is only present at low concentrations between 0.5 and 14 mg kg -1 (Table 2) irrespective of the total As body burden (Fig. 3b) suggests that AB formation is not a mechanism by which earthworms at DGC mitigate As toxicity.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…17 However, the fact that AB is only present at low concentrations between 0.5 and 14 mg kg -1 (Table 2) irrespective of the total As body burden (Fig. 3b) suggests that AB formation is not a mechanism by which earthworms at DGC mitigate As toxicity.…”
Section: Discussionmentioning
confidence: 93%
“…As III -sulphur complexes were detected in DGC earthworms by Langdon et al (2002) 17 when the in-situ speciation technique X-ray Absorption Spectroscopy (XAS) was employed. It is possible that the solvent extraction method employed in this study may cause 45 dissociation of As III -sulphur complexes leading to the detection As III alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of As-S complexes in the intestine has been well documented in earthworms. [26] Similarly, previous studies have shown that some metals tend to be concentrated in the midgut where they are stored in the form of granules [27,28] or in lysosomes. [29] Depuration of metals from the gut may occur when these storage structures are excreted from the body.…”
Section: Arsenic Speciation Using X-ray Absorption Spectroscopymentioning
confidence: 99%
“…Methanol-water extractions have been widely used for the extraction of arsenic species from biota samples, including earthworms [14][15][16][17] . Arsenite and arsenate were 60 demonstrated as the main extractable inorganic arsenicals in L. rubellus 15,18 . In most cases arsenobetaine (AB) is present as the primary organic arsenic species with methylarsonate (MA) present at trace levels 14,18 .…”
mentioning
confidence: 99%